Reusable thermal protection material and method of making

CN121427144BActive Publication Date: 2026-10-13WUHAN UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511745015.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-25
Publication Date
2026-10-13
Estimated Expiration
2045-11-25

AI Technical Summary

Technical Problem

[0005]有鉴于此,本发明提出了一种可重复使用热防护材料及其制备方法,以解决现有大面积可重复使用热防护材料的耐温等级不足、制备周期长和高温易分层技术问题

Benefits of technology

[0025]本发明提出了一种 “梯度复合、原位成瓷、功能分区” 的可重复使用梯度防隔热一体化热防护材料创新制备方法,采用分区浸渍与顺序固化的思路成功实现热压成型与溶胶-凝胶和常压干燥多工艺融合,以具有优异力学性能和抗冲刷能力的2.5D石英纤维平板织物为增强骨架,反应型可原位成瓷酚醛树脂和热塑性酚醛树脂为前驱体,构建了由表层反应型可原位成瓷防热复合材料与里层纳米多孔气凝胶隔热复合材料组成的整体式可重复使用梯度防隔热一体化热防护材料,实现了多尺度异质结构的精细构筑和可重复使用梯度防隔热一体化热防护材料的整体式便捷制备。在极端热氧环境下表层反应型可原位成瓷防热复合材料中的高炭型热固性酚醛树脂热裂解产生裂解炭、成瓷剂和氧气反应生成TiO、TiO2、SiO2、La2O3和B2O3等氧化物,进一步地氧化物之间、氧化物与裂解炭之间相互反应生成TiB2、TiC和SiC等超高温陶瓷,原位形成致密的含碳复相陶瓷层,实现从“被动烧蚀”到“主动生成热障层”的跨越。与此同时,里层纳米多孔气凝胶隔热复合材料承担高效隔热与轻量化的功能。解决了高效防热、隔热、轻量化、防热层和隔热层强界面结合以及承载的协同难题,达到在1200℃单侧高温加热1000s的极端服役条件下能够重复使用10次且背面温度不超过250℃的能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121427144B_ABST
    Figure CN121427144B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of heat protection materials, and particularly relates to a reusable heat protection material and a preparation method thereof, comprising the following steps: dispersing a porcelain forming agent in a high-carbon type thermosetting phenolic resin to obtain a reaction type in-situ porcelain forming phenolic resin precursor; impregnating a surface layer of a quartz fiber flat fabric in the reaction type in-situ porcelain forming phenolic resin precursor, removing the solvent after impregnation, and performing hot pressing forming treatment to make the surface layer form a reaction type in-situ porcelain forming heat protection composite material layer; impregnating an inner layer of the quartz fiber flat fabric in a thermoplastic phenolic resin precursor, and performing sol-gel and normal pressure drying process treatment to make the inner layer form a nano-porous aerogel heat insulation composite material layer, thereby obtaining the reusable heat protection material. The heat protection material prepared by the present application can be reused for 10 times under the extreme service condition of 1200 DEG C single-sided high temperature heating for 1000 s, and the back temperature does not exceed 250 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermal protection materials technology, and in particular to a reusable thermal protection material and its preparation method. Background Technology

[0002] Reusable hypersonic vehicles (such as hypersonic drones) experience severe aerodynamic heating during maneuvering, with temperatures reaching up to 1200°C over large areas, including their windward surfaces. Thermophysical ablation, thermochemical ablation, and thermomechanical erosion caused by high-temperature, high-speed, and high-pressure airflow can severely impact their structural integrity and strike accuracy. Achieving efficient and reliable reusable thermal protection is one of the bottlenecks restricting their development.

[0003] Traditional reusable thermal protection materials mainly include ceramic tiles, high-temperature alloys, and ceramic matrix composites. Ceramic tiles offer advantages such as light weight, low thermal conductivity, and oxidation resistance, but they are brittle, have poor damage resistance, and high maintenance costs. High-temperature alloys are easy to mold in large areas, but their temperature resistance is often below 1000℃, and they are prone to oxidation failure at high temperatures. Ceramic matrix composites have outstanding advantages in high-temperature resistance and oxidation resistance, but their production cycle is long, their cost is high, and it is difficult to achieve one-piece molding of irregularly shaped large-area components.

[0004] Patent CN 113619769 A proposes a reusable thermal protection structure combining phase change and decomposition heat absorption for aircraft. This structure integrates multiple heat protection methods, employing passive insulation, sweating cooling, convection cooling, or solid decomposition heat absorption depending on the aerodynamic thermal environment, thereby improving heat protection efficiency and material utilization, and extending the aircraft's service life. However, this structure is complex in overall construction, difficult to assemble, repair and replace, and has high manufacturing costs. Patent CN117866440 A discloses a reusable nanoporous hybrid resin-based thermal insulation material, which still exhibits excellent thermal insulation performance after being subjected to a 1000℃ static aerobic environment thermal test for 1000s and repeated 10 times. However, due to severe oxidation of the resin and its pyrolysis carbon, the upper limit of the material's operating temperature is insufficient to meet the requirements for efficient and reliable repetitive thermal protection for hypersonic UAVs at 1200℃. Patent CN 1191116478 A describes a quartz fiber-reinforced phenolic aerogel composite material with a dense surface layer. This material is created by needle-punching a surface woven fabric and an inner needle-punched felt layer, followed by sequential filling of the surface and inner matrix layers. The result is a composite material with ablation resistance, surface toughness, and thermal insulation properties. However, this preparation method involves a lengthy high-temperature heat treatment process, resulting in a long preparation cycle and demanding equipment requirements. Furthermore, the needle-punching process can damage the fibers and increase thermal conductivity channels. Under high-temperature, high-speed airflow and repeated service conditions, the surface woven fabric and inner needle-punched felt layer are prone to delamination and detachment. Summary of the Invention

[0005] In view of this, the present invention proposes a reusable thermal protection material and its preparation method to solve the technical problems of insufficient temperature resistance, long preparation cycle and easy delamination at high temperature of existing large-area reusable thermal protection materials.

[0006] The technical solution of this invention is achieved as follows: This invention provides a method for preparing a reusable thermal protection material, comprising the following steps:

[0007] S1. Disperse the ceramic-forming agent in a high-carbon thermosetting phenolic resin to obtain a reactive phenolic resin precursor that can be ceramicized in situ.

[0008] S2. The surface layer of the quartz fiber flat fabric is impregnated in a reactive in-situ ceramic phenolic resin precursor. After impregnation, the solvent is removed and the surface layer is hot-pressed to form a reactive in-situ ceramic heat-resistant composite material layer.

[0009] S3. The inner layer of the quartz fiber flat fabric is impregnated in a thermoplastic phenolic resin precursor and treated with a sol-gel and normal pressure drying process to form a nanoporous aerogel thermal insulation composite material layer, thus obtaining a reusable thermal protection material.

[0010] This invention employs an innovative method of impregnating different precursors onto a single 2.5D quartz fiber flat fabric in sections and then sequentially curing them. The surface reactive ceramic heat-resistant composite material and the inner nanoporous aerogel heat-insulating composite material form a strong interfacial bond through the fiber skeleton, achieving synergistic optimization of heat protection, heat insulation, lightweighting, strong interfacial bonding between the heat-resistant and heat-insulating layers, and load-bearing capacity. This successfully constructs an integrated, reusable, gradient heat-resistant and heat-insulating thermal protection material. Specifically, using a section impregnation technique, step S2 only impregnates the surface layer of the quartz fiber flat fabric with a reactive ceramic phenolic resin precursor. This allows the precursor to fully penetrate the fiber bundle gaps and achieve good wetting with the fibers. Under extreme thermo-oxidative environments, this surface material can generate a dense BCO-Si-Ti-La carbon-containing multiphase ceramic layer in situ. This ceramic layer, acting as a thermal barrier, effectively blocks oxygen diffusion into the interior, preventing further oxidation and ablation of the fibers and matrix, thereby achieving highly efficient heat protection on the surface. Step S3 utilizes the sol-gel reaction between thermoplastic phenolic resin and crosslinking agent in a solvent. Through the bridging effect of the crosslinking agent, the linear phenolic resin molecular chains form a three-dimensional network gel structure. During the solvent evaporation and drying process, the network skeleton shrinks and retains a large number of nanoscale pores. Finally, a nanoporous aerogel structure is constructed in situ in the inner fiber skeleton. This inner material undertakes the functions of high-efficiency heat insulation and lightweighting. The large number of nanoscale pores in its nanoporous structure effectively restricts gas convection and solid heat conduction, significantly reducing the overall thermal conductivity of the material.

[0011] Based on the above technical solutions, preferably, in step S1, by mass fraction, there are 100 parts of high-carbon thermosetting phenolic resin and 25-200 parts of ceramic-forming agent, wherein the ceramic-forming agent is a high-temperature ceramic.

[0012] Based on the above technical solutions, preferably, the ceramic forming agent is one or more combinations of binary boride ceramics, binary silicide ceramics, and ternary layered ceramics.

[0013] Specifically, high-carbon thermosetting phenolic resin can generate a large amount of pyrolyzed carbon during high-temperature pyrolysis. Meanwhile, the ceramic-forming agent reacts with oxygen under extreme thermo-oxidative conditions to generate oxides such as TiO, TiO2, SiO2, La2O3, and B2O3. Further reactions between these oxides and between the oxides and the pyrolyzed carbon produce ultra-high-temperature ceramics such as TiB2, TiC, and SiC, thus laying the material foundation for the subsequent in-situ formation of a dense carbon-containing multiphase ceramic layer. The optimal mass ratio of the ceramic-forming agent to the high-carbon thermosetting phenolic resin ensures that the resin pyrolysis generates sufficient pyrolyzed carbon as a carbon source while also ensuring a sufficient content of the ceramic-forming agent to achieve an efficient ceramicization reaction. This represents a leap from "passive ablation" to "active generation of a thermal barrier layer," significantly improving the material's oxidation resistance and high-temperature resistance.

[0014] Based on the above technical solutions, preferably, the high-carbon thermosetting phenolic resin is one or more of boron phenolic resin, silicone phenolic resin and benzoxazine resin.

[0015] Based on the above technical solutions, preferably, the ceramic-forming agent comprises ternary layered ceramic and binary boride ceramic, with a mass ratio of (45~55):15 between the ternary layered ceramic and the binary boride ceramic. More preferably, the mass ratio of the ternary layered ceramic and the binary boride ceramic is 50:15, wherein the ternary layered ceramic is Ti3SiC2 and the binary boride ceramic is LaB6.

[0016] Based on the above technical solutions, preferably, in step S2, the quartz fiber flat fabric is a 2.5D quartz fiber flat fabric, and the surface layer thickness is 10%-40% of the thickness of the 2.5D quartz fiber flat fabric.

[0017] Based on the above technical solutions, preferably, in step S2, the process parameters for hot pressing molding include: first, pre-treating at 80-120℃ for 10-60 min, then curing at 140-180℃ for 90-180 min, and finally post-curing at 190-220℃ for 60-120 min.

[0018] After solvent removal, the resin matrix is ​​cured in stages under ambient pressure through a hot pressing molding process, which fully cross-links and cures the resin matrix to form a three-dimensional network structure. At the same time, the pressure removes air bubbles and reduces porosity, resulting in a dense surface reactive in-situ ceramic heat-resistant composite material with high bonding strength with the fiber interface.

[0019] Based on the above technical solutions, preferably, in step S3, the thermoplastic phenolic resin precursor includes thermoplastic phenolic resin, hexamethylenetetramine, and n-propanol, with a mass ratio of (55~65):10:230. More preferably, the mass ratio of thermoplastic phenolic resin, hexamethylenetetramine, and n-propanol is 60:10:230.

[0020] Based on the above technical solutions, preferably, in step S3, the process parameters for the sol-gel treatment include: first, heating to 75~85℃ and reacting the sol-gel for 1050~1110 min, then cooling to 20~30℃ and aging for 1400~1480 min. More preferably, the sol-gel process involves reacting the sol-gel at 80℃ for 1080 min under ambient pressure and aging at 25℃ for 1440 min.

[0021] Based on the above technical solutions, preferably, in step S3, the process parameters for atmospheric pressure drying include: drying at 55~65℃ for 550~650 min, drying at 75~85℃ for 700~740 min, and drying at 95~105℃ for 220~260 min sequentially. More preferably, the atmospheric pressure drying process is drying at 60℃ for 600 min, drying at 80℃ for 720 min, and drying at 100℃ for 240 min under ambient pressure.

[0022] The sol-gel and atmospheric pressure drying process is carried out in stages under environmental pressure: first, the cross-linking is fully completed through the sol-gel reaction, then the strength of the gel network is enhanced, and then the gradient temperature drying is carried out in sequence to gently remove the solvent while keeping the nanoporous structure from collapsing, forming a low-density, low-thermal-conductivity nanoporous aerogel thermal insulation composite material layer.

[0023] The present invention also provides a reusable thermal protection material prepared by the preparation method described above, wherein the reusable thermal protection material can be reused 10 times under extreme service conditions of unilateral high temperature heating at 1200°C for 1000s and the back surface temperature does not exceed 250°C.

[0024] The reusable thermal protection material and its preparation method of the present invention have the following advantages over the prior art:

[0025] This invention proposes an innovative preparation method for a reusable gradient thermal insulation integrated thermal protection material featuring "gradient composite, in-situ ceramic formation, and functional zoning." It successfully integrates hot pressing, sol-gel, and atmospheric pressure drying processes using a zonal impregnation and sequential curing approach. A 2.5D quartz fiber flat fabric with excellent mechanical properties and erosion resistance serves as the reinforcing skeleton, while reactive in-situ ceramic phenolic resin and thermoplastic phenolic resin are used as precursors. This constructs an integral, reusable gradient thermal insulation integrated thermal protection material consisting of a surface reactive in-situ ceramic thermal insulation composite material and an inner nanoporous aerogel thermal insulation composite material. This method achieves the precise construction of multi-scale heterogeneous structures and the convenient, integral preparation of the reusable gradient thermal insulation integrated thermal protection material. In extreme thermo-oxidative environments, the high-carbon thermosetting phenolic resin in the surface reactive in-situ ceramic thermal insulation composite material undergoes thermal decomposition to produce cracked carbon. This carbon, along with the ceramic-forming agent and oxygen, reacts to generate oxides such as TiO, TiO2, SiO2, La2O3, and B2O3. Further reactions between these oxides, and between the oxides and the cracked carbon, generate ultra-high temperature ceramics such as TiB2, TiC, and SiC, forming a dense, carbon-containing multiphase ceramic layer in situ. This represents a leap from "passive ablation" to "active generation of a thermal barrier layer." Simultaneously, the inner nanoporous aerogel thermal insulation composite material provides both high-efficiency thermal insulation and lightweighting. This solution addresses the challenges of high-efficiency thermal protection, insulation, lightweighting, strong interfacial bonding between the thermal protection and insulation layers, and synergistic load-bearing capacity. It achieves the capability to be reused 10 times under extreme service conditions of 1200℃ single-sided high-temperature heating for 1000s with the back surface temperature not exceeding 250℃. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 This is a photograph of the butane flame test result of the thermal protection material in Example 1 of the present invention.

[0028] Figure 2 This is a diagram showing the microstructure and elemental distribution of the butane flame test results of the thermal protection material in Example 1 of this invention.

[0029] Figure 3 This is a photograph of the butane flame test result of the thermal protection material in Comparative Example 1 of the present invention.

[0030] Figure 4 This is a diagram showing the microstructure and elemental distribution of the butane heat protection material in Comparative Example 1 of the present invention after flame testing. Detailed Implementation

[0031] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0032] Example 1 This embodiment provides a reusable thermal protection material and its preparation method, including the following steps:

[0033] S1. Disperse 50 parts of Ti3SiC2 and 15 parts of LaB6 in 100 parts of boron phenolic resin to obtain a reactive phenolic resin precursor that can be used for in-situ ceramic formation.

[0034] S2. A 3 mm surface layer of a 20 mm thick 2.5D quartz fiber flat fabric is impregnated with a reactive in-situ ceramic phenolic resin precursor. After solvent removal, a surface reactive in-situ ceramic preform is obtained. Then, it is pretreated at 120°C for 15 min, cured at 160°C for 120 min, and post-cured at 200°C for 60 min under ambient pressure to obtain a surface reactive in-situ ceramic heat-resistant composite material.

[0035] S3. Impregnate a 17 mm inner layer of a 2.5D quartz fiber flat fabric with a thermoplastic phenolic resin precursor (formed by thermoplastic phenolic resin, hexamethylenetetramine, and n-propanol in a ratio of 60:10:230). Then, subject the fabric to the following treatments under ambient pressure: sol-gel reaction at 80°C for 1080 min, aging at 25°C for 1440 min, drying at 60°C for 600 min, drying at 80°C for 720 min, and drying at 100°C for 240 min. This process yields a nanoporous aerogel thermal insulation composite material for the inner layer, ultimately resulting in a reusable thermal protection material.

[0036] Example 2 This embodiment provides a reusable thermal protection material and its preparation method, including the following steps:

[0037] S1. Disperse 19 parts of Ti3SiC2 and 6 parts of LaB6 in 100 parts of boron phenolic resin to obtain a reactive phenolic resin precursor that can be used for in-situ ceramic formation.

[0038] S2. A 20 mm thick 2.5D quartz fiber flat fabric is impregnated with a reactive in-situ ceramic phenolic resin precursor. After solvent removal, a surface reactive in-situ ceramic preform is obtained. Then, it is pretreated at 80°C for 60 min, cured at 140°C for 180 min, and post-cured at 190°C for 120 min under ambient pressure to obtain a surface reactive in-situ ceramic heat-resistant composite material.

[0039] S3. Impregnate an 18 mm inner layer of a 2.5D quartz fiber flat fabric with a thermoplastic phenolic resin precursor (formed by thermoplastic phenolic resin, hexamethylenetetramine, and n-propanol in a ratio of 55:10:230), and then subject it to the following treatments under ambient pressure: sol-gel reaction at 75°C for 1110 min, aging at 20°C for 1480 min, drying at 55°C for 650 min, drying at 75°C for 740 min, and drying at 95°C for 260 min to obtain an inner layer nanoporous aerogel thermal insulation composite material, ultimately yielding a reusable thermal protection material.

[0040] Example 3 This embodiment provides a reusable thermal protection material and its preparation method, including the following steps:

[0041] S1. 154 parts of Ti3SiC2 and 46 parts of LaB6 were dispersed in 100 parts of boron phenolic resin to obtain a reactive phenolic resin precursor that can be used to form ceramics in situ.

[0042] S2. An 8 mm surface layer of a 20 mm thick 2.5D quartz fiber flat fabric is impregnated with a reactive in-situ ceramic phenolic resin precursor. After solvent removal, a surface reactive in-situ ceramic preform is obtained. Then, it is pretreated at 100°C for 10 min, cured at 140°C for 90 min, and post-cured at 220°C for 90 min under ambient pressure to obtain a surface reactive in-situ ceramic heat-resistant composite material.

[0043] S3. Impregnate a 12 mm inner layer of a 2.5D quartz fiber flat fabric with a thermoplastic phenolic resin precursor (formed by thermoplastic phenolic resin, hexamethylenetetramine, and n-propanol in a ratio of 65:10:230). Then, subject the fabric to the following treatments under ambient pressure: sol-gel reaction at 85°C for 1050 min, aging at 30°C for 1400 min, drying at 65°C for 550 min, drying at 85°C for 700 min, and drying at 105°C for 220 min. This process yields a nanoporous aerogel thermal insulation composite material for the inner layer, ultimately resulting in a reusable thermal protection material.

[0044] Comparative Example 1 This comparative example provides a thermal protection material and its preparation method. The difference between this material and Example 1 is that it lacks a reactive phenolic resin precursor that can be used to form ceramics in situ. The specific steps include:

[0045] A 20mm thick 2.5D quartz fiber flat fabric was impregnated with a thermoplastic phenolic resin precursor (formed by thermoplastic phenolic resin, hexamethylenetetramine, and n-propanol in a ratio of 60:10:230). The fabric was then subjected to the following treatments under ambient pressure: sol-gel reaction at 80°C for 1080 min, aging at 25°C for 1440 min, drying at 60°C for 600 min, drying at 80°C for 720 min, and drying at 100°C for 240 min. This process yielded an inner layer of nanoporous aerogel thermal insulation composite material, ultimately resulting in a thermal protection material.

[0046] Comparative Example 2 This comparative example provides a thermal protection material and its preparation method, which differs from Example 1 in that it lacks LaB6. Specifically, it includes the following steps:

[0047] S1. Disperse 50 parts of Ti3SiC2 in 100 parts of boron phenolic resin to obtain a reactive phenolic resin precursor that can be used for in-situ ceramic formation.

[0048] S2~S3 are the same as in Example 1.

[0049] Comparative Example 3 This comparative example provides a thermal protection material and its preparation method, which differs from Example 1 in that it lacks Ti3SiC2. Specifically, it includes the following steps:

[0050] S1. Disperse 15 parts of LaB6 in 100 parts of boron phenolic resin to obtain a reactive phenolic resin precursor that can be used for in-situ ceramic formation.

[0051] S2~S3 are the same as in Example 1.

[0052] Comparative Example 4 This comparative example provides a thermal protection material and its preparation method. The difference between this example and Example 1 is the absence of a nanoporous aerogel thermal insulation composite material. Specifically, it includes the following steps:

[0053] S1. Disperse 50 parts of Ti3SiC2 and 15 parts of LaB6 in 100 parts of boron phenolic resin to obtain a reactive phenolic resin precursor that can be used for in-situ ceramic formation.

[0054] S2. A 20 mm thick 2.5D quartz fiber flat fabric is impregnated with a reactive in-situ ceramic phenolic resin precursor. After solvent removal, a surface reactive in-situ ceramic preform is obtained. Then, it is pretreated at 120°C for 15 min, cured at 160°C for 120 min, and post-cured at 200°C for 60 min under ambient pressure to obtain a heat protection material.

[0055] Performance testing The thermal protection material samples prepared in the examples and comparative examples were tested for compressive strength, density and thermal conductivity. The residual weight of the thermal protection material samples was tested at 1200°C in air atmosphere. The test results are shown in Table 1.

[0056] Table 1

[0057]

[0058] The thermal protection material was placed at 1.5 MW / m 2 The thermal protection material was tested under an oxy-acetylene flame for 120 s to detect the ablation rate and back surface temperature. The material was then tested under a butane flame at 1200℃ for 1000 s, and this test was repeated 10 times to examine the surface condition of the sample. The test results are shown in Table 2.

[0059] Table 2

[0060]

[0061] Figure 1 The image shows a physical photograph of the thermal protection material from Example 1 after being subjected to a butane flame test at 1200°C for 1000 seconds, repeated 10 times. Figure 1 It can be seen that a dense ceramic layer is formed on the sample surface, the overall structure is intact, and there are no obvious deformations, cracks, or delamination phenomena.

[0062] Figure 2 The microstructure and elemental distribution of the thermal protection material in Example 1 after being subjected to a butane flame test at 1200°C for 1000 seconds and repeated 10 times are shown. Figure 2 In the figure, Figure (a) shows the microstructure at 100x magnification, Figure (b) shows the elemental distribution, Figure (c) shows the elemental content, and Figures (d) to (i) show the distribution of C, B, O, Si, Ti, and La. Figure 2 It can be seen that a dense BCO-Si-Ti-La carbon-containing multiphase ceramic layer was formed on the sample surface, without obvious cracks, pores, or pits;

[0063] Figure 3 The image shows the physical product of the heat protection material in Comparative Example 1 after being subjected to a butane flame test at 1200°C for 1000 seconds, repeated 10 times. Figure 3 It can be seen that the fibers on the sample surface are directly exposed, with no obvious carbon residue;

[0064] Figure 4 The microstructure and elemental distribution of the thermal protection material in Comparative Example 1 after being subjected to a butane flame test at 1200°C for 1000 s and repeated 10 times are shown. Figure 4 In the figure, Figure (a) shows the microstructure at 100x magnification, Figure (b) shows the microstructure at 700x magnification, and Figure (c) shows the microstructure at 10000x magnification. There is very little residual carbon on the sample surface, and the fibers are severely damaged.

[0065] As shown in Tables 1 and 2, the reusable gradient heat protection material prepared by the technical solution of the present invention solves the problems of efficient heat protection, heat insulation, lightweight, strong interface bonding between the heat protection layer and the heat insulation layer, and load-bearing synergy. It can be reused 10 times under extreme service conditions of 1200℃ single-sided high temperature heating for 1000s and the back temperature does not exceed 250℃.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a reusable thermal protection material, characterized in that, Includes the following steps: S1. Disperse the ceramic-forming agent in a high-carbon thermosetting phenolic resin to obtain a reactive phenolic resin precursor that can form ceramics in situ. S2. The surface layer of the quartz fiber flat fabric is impregnated in a reactive in-situ ceramic phenolic resin precursor. After impregnation, the solvent is removed and the surface layer is hot-pressed to form a reactive in-situ ceramic heat-resistant composite material layer. S3. The inner layer of the quartz fiber flat fabric is impregnated in a thermoplastic phenolic resin precursor and treated with sol-gel and normal pressure drying processes to form a nanoporous aerogel thermal insulation composite material layer, thus obtaining a reusable thermal protection material. In step S1, by mass fraction, there are 100 parts of high-carbon thermosetting phenolic resin and 25-200 parts of ceramic forming agent. The ceramic forming agent includes ternary layered ceramics and binary boride ceramics, and the mass ratio of ternary layered ceramics to binary boride ceramics is (45~55):

15.

2. The method for preparing a reusable thermal protection material as described in claim 1, characterized in that: The high-carbon thermosetting phenolic resin is one or more of boron phenolic resin, silicone phenolic resin and benzoxazine resin.

3. The method for preparing a reusable thermal protection material as described in claim 1, characterized in that: In step S2, the quartz fiber flat fabric is a 2.5D quartz fiber flat fabric, and the surface layer thickness is 10%-40% of the thickness of the 2.5D quartz fiber flat fabric.

4. The method for preparing a reusable thermal protection material as described in claim 1, characterized in that: In step S2, the process parameters for hot pressing include: first, pre-treating at 80-120℃ for 10-60 min, then curing at 140-180℃ for 90-180 min, and finally post-curing at 190-220℃ for 60-120 min.

5. The method for preparing a reusable thermal protection material as described in claim 1, characterized in that: In step S3, the thermoplastic phenolic resin precursor includes thermoplastic phenolic resin, hexamethylenetetramine, and n-propanol, with a mass ratio of 55~65:10:

230.

6. The method for preparing a reusable thermal protection material as described in claim 1, characterized in that: In step S3, the process parameters for sol-gel treatment include: first, heating to 75~85℃ for sol-gel reaction for 1050~1110 min, and then cooling to 20~30℃ for aging for 1400~1480 min; the process parameters for atmospheric pressure drying treatment include: drying at 55~65℃ for 550~650 min, drying at 75~85℃ for 700~740 min, and drying at 95~105℃ for 220~260 min in sequence.

7. The reusable thermal protection material prepared by the preparation method according to any one of claims 1 to 6, wherein the reusable thermal protection material can be reused 10 times under extreme service conditions of unilateral high temperature heating at 1200°C for 1000s and the back surface temperature does not exceed 250°C.

Citation Information

Patent Citations

  • Phase change heat absorption and decomposition heat absorption composite reusable thermal protection structure of aircraft

    CN113619769A

  • Nano-pore hybrid resin-based heat prevention and insulation material capable of being repeatedly used for limited times and preparation method of nano-pore hybrid resin-based heat prevention and insulation material

    CN117866440A

  • Nanoporous antioxidant resin-based composite material and preparation method thereof

    CN111040375A

  • Heat protection, heat insulation and bearing integrated light carbon-ceramic composite material as well as preparation and application of heat protection, heat insulation and bearing integrated light carbon-ceramic composite material

    CN117819999A